2021
DOI: 10.3329/brc.v7i2.54378
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of biomarkers of expired and cured COVID- 19 ICU patients in a tertiary care hospital

Abstract: Coronavirus Disease 2019 (COVID-19) is a respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2). This is a retrospective observational study aimed to find the alteration of some biochemical and hematological parameters of 121 COVID-19 patients admitted in intensive care unit (ICU) of Evercare Hospital Dhaka during May to December 2020. Methods: Retrospective biochemical, hematological and molecular (COVID-19 RT-PCR Ct value) markers were analyzed on COVID-19 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…No significant differences were observed in ALT and platelet values (Table 2 and Figure S1). These results were consistent with numerous previous studies [46][47][48][49][50][51][52][53][54][55][56][57][58] and confirmed that the patients were grouped appropriately.…”
Section: Laboratory Findingssupporting
confidence: 93%
“…No significant differences were observed in ALT and platelet values (Table 2 and Figure S1). These results were consistent with numerous previous studies [46][47][48][49][50][51][52][53][54][55][56][57][58] and confirmed that the patients were grouped appropriately.…”
Section: Laboratory Findingssupporting
confidence: 93%